Virotherapy - Cancer targeted pharmacology - Tedcastle, A; Cawood, R; Di, Y; Fisher, K; Seymour, L (2012)
Building on their success in vaccination, many groups are now exploring the use of viruses as anticancer agents. In general, viral therapeutics provide the possibility to express anticancer proteins directly at the tumour site, decreasing exposure to normal tissue during delivery and maximising therapeutic index. Some viruses are also 'oncolytic', either naturally or by design, and these agents function to kill cancer cells selectively before spreading to infect adjacent cells and repeat the process. This whole field of cancer 'virotherapy' is moving forward rapidly at the moment, with notable clinical successes demonstrated with a range of oncolytic agents developed as directly oncolytic and also as oncolytic cancer vaccines. Given the versatility of oncolytic viruses to express therapeutic proteins we anticipate this approach will provide the platform for useful application of a broad range of innovative biological therapies. © 2012 Elsevier Ltd.